Bovid ecomorphology and hominin paleoenvironments of the Shungura Formation, lower Omo River Valley, Ethiopia. Issue 88 (November 2015) - Plummer, Thomas W.; Ferraro, Joseph V.; Louys, Julien; Hertel, Fritz; Alemseged, Zeresenay; Bobe, René; Bishop, L.C.
Abstract: The Shungura Formation in the lower Omo River Valley, southern Ethiopia, has yielded an important paleontological and archeological record from the Pliocene and Pleistocene of eastern Africa. Fossils are common throughout the sequence and provide evidence of paleoenvironments and environmental change through time. This study developed discriminant function ecomorphology models that linked astragalus morphology to broadly defined habitat categories (open, light cover, heavy cover, forest, and wetlands) using modern bovids of known ecology. These models used seven variables suitable for use on fragmentary fossils and had overall classification success rates of >82%. Four hundred and one fossils were analyzed from Shungura Formation members B through G (3.4–1.9 million years ago). Analysis by member documented the full range of ecomorph categories, demonstrating that a wide range of habitats existed along the axis of the paleo-Omo River. Heavy cover ecomorphs, reflecting habitats such as woodland and heavy bushland, were the most common in the fossil sample. The trend of increasing open cover habitats from Members C through F suggested by other paleoenvironmental proxies was documented by the increase in open habitat ecomorphs during this interval. However, finer grained analysis demonstrated considerable variability in ecomorph frequencies over time, suggesting that substantial short-term variability is masked when grouping samples by member. The hominin genera Australopithecus, Homo, and Paranthropus are associated with a range of ecomorphs, indicating that all three genera were living in temporally variable and heterogeneous landscapes. Australopithecus finds were predominantly associated with lower frequencies of open habitat ecomorphs, and high frequencies of heavy cover ecomorphs, perhaps indicating a more woodland focus for this genus.